THAI LEADER, DHARMA LEADER, BUDDHIST LEADER - Lertsaphan, Umarin; Thitapanyo, PhramahaMit (Journal of Graduate MCU KhonKaen Campus, 2021)
The Book is Thai leaders, Dharma leaders, and Buddhist leaders that describes the leadership of Thailand, both there are the Civil servant and city officials. It is a book to build relationships between one another, leaders and those under your control for change. The transition must be requires principles to bring change balanced that physically, Mental and environmental. The application of the Dhamma principles in the administration and development of the country to prosper and create peace for the society. In addition to the Buddhist leadership that a leader in morality, morality, and ethics. This is a describe book of Thai leaders, Dharma leaders, Buddhist leaders for importing the system development with the present time.